2015
DOI: 10.3389/fpsyg.2015.01567
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary evaluation of an analog procedure to assess acceptability of intimate partner violence against women: the Partner Violence Acceptability Movie Task

Abstract: Acceptability of partner violence against women is a risk factor linked to its perpetration, and to public, professionals’ and victims’ responses to this behavior. Research on the acceptability of violence in intimate partner relationships is, however, limited by reliance solely on self-reports that often provide distorted or socially desirable accounts that may misrepresent respondents’ attitudes. This study presents data on the development and initial validation of a new analog task assessing respondents’ ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
73
1
11

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(95 citation statements)
references
References 55 publications
10
73
1
11
Order By: Relevance
“…Moreover, the correlations among the subscales followed the pattern found in previous research (e.g. Gracia et al, 2015); JPV was positively related to VRV and negatively related to ARV, whilst VRV and ARV were negatively correlated.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Moreover, the correlations among the subscales followed the pattern found in previous research (e.g. Gracia et al, 2015); JPV was positively related to VRV and negatively related to ARV, whilst VRV and ARV were negatively correlated.…”
Section: Discussionsupporting
confidence: 81%
“…Nevertheless, it is worth noting that the correlations between constructs were higher for men than for women. This is not surprising as research has shown that women tend to express stronger disapproval of wife beating than men (Gracia et al, 2015;Sakalli, 2001;Valor-Segura et al, 2011) and also attribute less blame to the victim and more to the perpetrator (Strömwall, Landström, & Alfredsson, 2014) .…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In line with these results, previous studies have demonstrated that violent offenders show significant deficits in attentional set shifting or larger attention switch costs in comparison with non-violent population (Bergvall, Wessely, Forsman, & Hansen, 2001). In fact, this attention deficit might explain not only the impaired emotion decoding process but also the executive domain deficits defined as a worse performance in tests like the Wisconsin Card Sorting Test, which has been previously reported in IPV perpetrators (Gracia et al, 2015;Romero-Martínez, Lila, Catalá-Miñana et al, 2013;Romero-Martínez, Lila, Sariñana-González et al, 2013;. Nonetheless, it is important to note that in our research we analyzed attention deficits with self-reports, although these subscales have been employed as successful inattention measures in previous studies in several populations (Polderman et al, 2013;Rusconi, Ferri, Viding, & Mitchener-Nissen, 2015;Sizoo et al, 2009).…”
Section: Discussionsupporting
confidence: 82%
“…Należy zatem zastanowić się, czy płeć nie pełni funkcji moderatora powiązań między empatią a postawami wobec przemocy. Empatia i agresja to dwa obszary różnic indywidualnych, w obrębie których stwierdza się znaczące różnice międzypłciowe, kojarzone głównie z oddziaływaniem wpływów kulturowych i socjalizacyjnych (Mandal, 2003) Przy tym kobiety uzyskują wyższe wskaźniki na skalach empatii, zwłaszcza emocjonalnej (Eisenberg, Lennon, 1983, Mandal, 2005, a mężczyź-ni w obszarze zachowań agresywnych, jak i akceptacji przemocy, w tym wobec kobiet w związku (Gracia, Rodriguez, Lila, 2015;Pastwa-Wojciechowska i in., 2013). Przywołane powyżej wyniki badań pozostają w zgodzie z tezami dotyczą-cymi powiązań między brakiem empatii i akceptacją przemocy wśród mężczyzn w grupach klinicznych, m.in.…”
unclassified